Pelatihan dan Pendampingan Branding Berbasis Digital sebagai Upaya Pengembangan UMKM Di Kelurahan Bulak Banteng - Amir, Faradila; Rahmani Santosa, Dian; Febrianita, Roziana (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
MSMEs or Micro, Small and Medium Enterprises are one of the factors that help improve the economy in Indonesia, both the micro and macro economy. Currently, there are many people who have MSMEs with various kinds of creative products that are sold. However, the development of MSMEs has experienced several obstacles, one of which is the lack of knowledge of MSME actors in utilizing information and communication technology that has developed, such as lack of knowledge about product branding. Branding is an attempt to produce an impression that attracts consumers. Lack of branding efforts can make MSME products less competitive in the market. For this reason, in an effort to develop MSMEs in Bulak Banteng through a digital-based branding strategy, this community service activity is carried out in several stages, namely counseling, training and mentoring, and the last stages is evaluation. From this activity, it is known that several MSMEs, namely Rumah Batik Jawa Timur, Mie Ramingkem, Pawone Mamiku, and UMKM Sumberejo have understood how important branding is for a product, this can be seen from the use of social media which has been better than before